Knowledge, Beliefs, and Behaviors of Turkish Parents about Childhood Vaccination - Zuhal Emlek Sert; Sevcan Topçu; Aysun Çelebioğlu (MDPI AG, 2023)
Background and Objectives: Vaccination is critical to the prevention and control of infectious disease outbreaks and is also one of the most important public health successes. When it comes to childhood vaccinations, parents' consent is very important. For this reason, childhood vaccination rates are directly related to the knowledge, beliefs, and behaviors of the parents. Therefore, this study aimed to evaluate the knowledge, beliefs, and behaviors of parents of children aged 0-5 regarding childhood vaccinations and how these beliefs affect their vaccination behaviors. Material and Methods: This descriptive, cross-sectional study was conducted on 302 parents from February to June 2020. Data were collected using a questionnaire form with 26 questions. Sociodemographic characteristics were reported as frequencies, means, and percentages. Multiple regression analysis was utilized to evaluate vaccination behaviors and affective factors. Results: About 87.1% of the parents know that vaccines protect their children from infectious diseases, and 76.8% know that vaccines can have side effects. Although 97.7% of the parents had their children fully vaccinated according to the Extended Immunization Program, 2.3% did not vaccinate their children. Moreover, 98% of the parents trust the information given by healthcare professionals about vaccination. The parents' beliefs explain 53% (R2 = 0.53) of the parents' child vaccination behavior. Conclusion: This study found that although the knowledge level of parents about vaccines is quite good, negative knowledge and beliefs that may affect vaccination also exist. Considered by parents as a reliable source of information, healthcare professionals should impart their knowledge, beliefs, and concerns regarding immunization.